2015
DOI: 10.1007/s11356-015-5273-1
|View full text |Cite
|
Sign up to set email alerts
|

A review of soil cadmium contamination in China including a health risk assessment

Abstract: Cadmium (Cd) is one of the most serious soil contaminants in China, and it poses an increasing risk to human health as large amounts of Cd are emitted into the environment. However, knowledge about soil Cd concentrations and the human health risks of these concentrations at a national scale is limited. In this study, we conducted a review of 190 articles about soil Cd concentrations during 2001 to 2010. The study involved 146 cities in China, and we quantified the risks to human health according to different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(69 citation statements)
references
References 24 publications
2
67
0
Order By: Relevance
“…The soil content of the heavy metals studied ranged from 0.038 to 225.7 mg kg −1 (Table 2). The mean values (across all soil samples) were all lower than the Chinese national soil environmental quality standard (Wang et al, 2015). One sample point of Ni and three sample points of Cd exceeded the national secondary standard for soil environmental quality.…”
Section: Resultsmentioning
confidence: 61%
“…The soil content of the heavy metals studied ranged from 0.038 to 225.7 mg kg −1 (Table 2). The mean values (across all soil samples) were all lower than the Chinese national soil environmental quality standard (Wang et al, 2015). One sample point of Ni and three sample points of Cd exceeded the national secondary standard for soil environmental quality.…”
Section: Resultsmentioning
confidence: 61%
“…Although the adverse health effects of Cd are wellknown and the underlying mechanisms have been disclosed in degrees (see our review: Koedrith and Seo, 2011;Kwon et al, 2013;Kim et al, 2015), exposure to Cd is still being reported in some parts of the world (Ikeda et al, 2004;Pan et al, 2010;Waseem et al, 2014;Wang et al, 2015;Johnson et al, 2016). In addition to its discharge from mines, the emission of Cd has markedly increased since the late 20th century.…”
Section: Resultsmentioning
confidence: 98%
“…It was reported by the Ministry of Environmental Protection, P. R. China, that as of 2014, 7% of all cultivated areas contained Cd-contaminated soil. There is growing concern regarding Cd contamination because excess Cd exposure can directly cause both noncarcinogenic and carcinogenic risks 2 . Cd in soils can be readily taken up by plant roots and transferred to aboveground plant parts, resulting in phytotoxicity, which will indirectly cause a threat to animal and human health through the food chain [2][3][4][5] .…”
Section: The Effectiveness Of Nanobiochar For Reducing Phytotoxicity mentioning
confidence: 99%